PENGEMBANGAN PEMBELAJARAN BERBASIS HOTS (HIGHER ORDER THINKING SKILL) DI SEKOLAH DASAR KELAS V - Fanani, Ahmad; Kusmaharti, Dian (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2018)
Abstract: One element of the transformation of the 2013 curriculum at the primary school level is the strengthening of integrated learning processes and thematic applications using a scientific approach and familiarizing the development of high-order thinking skills (HOTS) for students. This research uses a prototype model of instructional development with reference to the Dick and Carry learning development model. Data collection techniques used were questionnaires and tests. The limited trial results indicate that learning development outcomes are able to produce total learning outcomes (91%) in Lesson 1, Sub-themes 3, Human and Natural Events, Theme of Activity in Primary Class V Life. Keywords: Learning Model, Higher Order Thinking Skill, Elementary School Abstrak : Salah satu elemen transformasi kurikulum 2013 di tingkat sekolah dasar adalah penguatan proses pembelajaran dan penerapan tematik terintegrasi dengan menggunakan pendekatan saintifik dan mengakrabkan pengembangan keterampilan berpikir tingkat tinggi (HOTS) bagi siswa. Penelitian ini mengguakan model prototipe pengembangan pembelajaran dengan mengacu pada model pengembangan pembelajaran Dick dan Carry. Teknik pengumpulan data yang digunakan adalah angket dan tes. Hasil uji coba yang terbatas menunjukkan bahwa hasil pengembangan pembelajaran mampu menghasilkan hasil belajar total (91%) dalam pembelajaran 1, Sub-tema 3, Peristiwa Manusia dan Alam, Tema Kegiatan dalam Kehidupan kelas V Sekolah Dasar. Kata kunci : Model Pembelajaran, Higher Order Thinking Skill, Sekolah Dasar